OPTIMASI SALINITAS DAN pH AWAL MEDIA BG-11 TERHADAP KONSENTRASI BIOMASSA Tetraselmis chuii - Ayu Adi, Ida; Dewi Anggreni, A.A.Made; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aim of this study was to determine the optimum points of salinity and pH on BG-11 medium to produce maximum yields of biomass of marine microalgae Tetraselmis chuii. The optimization was performed using Response Surface Methodology (RSM), and Central Composite Design (CCD) was used to study the effects of the optimum salinity and pH on biomass of Tetraselmis chuii. The results showed that the optimum points of initial salinity and pH on BG-11 medium to produce maximum yields of biomass of 2.42 x 10 6 cell/mL were 42.06‰ and 8.23, respectively. The optimization obtained a regression model of Z = -1.039 + 0.045X – 0.0004X 2 + 0.614Y – 0.034 Y 2 – 0.001XY + 0, with coefficient determination of 0.97005. The validation using T test showed there were no difference between the actual and regression model based score, with p score of 0.14 for biomass concentration of marine microalgae Tetraselmis chuii. Keywords: BG-11, biomass, pH, salinity, Tetraselmis chuii.
Keywords: 72